On the assessment of non-metallic inclusions by part 13 of API 579 -1/ASME FFS-1 2016 - Jorge Luis González-Velázquez; Ehsan Entezari; Jerzy A. Szpunar (Fracture and Structural Integrity)
Improvement of nondestructive inspection techniques has allowed more frequent detection of closely spaced zones of non-metallic inclusions in pressure vessels made of low carbon steel. In the present study, closely spaced inclusions in an in-service cylindrical horizontal pressure vessel were detected by Scan-C ultrasonic inspection and considered as laminations to be assessed by Part 13 of the API 579-1/ASME FFS-1 2016 standard. The outcoming results were considered as a rejection for Level 1 assessment, and a repair or replacement of the component was required, even though it retained a significant remaining strength. Thus, an alternative procedure to assess the mechanical integrity of pressure vessels containing zones of non-metallic inclusions is proposed by adopting some criteria of the API 579-1/ASME FFS-1 Part 13 standard procedure and taking into consideration the dimensions and grouping characteristics of the inclusion zones.